Electric-field Control of a Spin “bit” Configuration in MERAM Model: A Monte Carlo Study - Dung, Tran Viet; Long, Dang Dinh (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: Magnetoelectric (ME) effect can be realized in multiferroic composites composed of the alternative ferromagnetic (FM) and ferroelectric (FE) multilayer such as FM layer grown on top of FE layer (FM/FE). In this work, we have shown that the spin orientation in FM layer can be controlled by using the electrical field indirectly via the elastic mechanism between these layers. There is a critical electric field  for each FM layer such as Fe, Fe 3 O 4 , which is the minimum electric field to switch the spin to the different directions in space. TheMonte Carlo simulation has been applied for the anisotropy model taken into account the magnetocrystalline anisotropy and shape anisotropy as well as the effective anisotropy field. The particular spin switching, i.e. an angle of 90 degree switching, corresponding to bit “0” and “1” switching in magnetoelectric random access memory (MERAM) will be discussed. Keywords : magnetoelectric effect, multiferroic composites, electric-field control of magnetism, anisotropy model, Monte Carlo simulation, MERAM